Trajektori Branding Politik di Indonesia: dari Kampanye Konvensional ke Politik Performatif di Media Sosial - Adila, Isma; Eddyono , Aryo Subarkah (Journal of Politics and Policy, 2025)
Indonesia’s political branding has undergone significant shifts as social media emerges as a dominant force in political communication. No longer limited to message distribution, platforms like Facebook, Twitter (X), Instagram, official websites, and TikTok have become spaces where political identities are constructed, narratives are shaped, and emotional bonds with voters are cultivated. This study analyzes five presidential election cycles (2009–2024) using Andreas Hepp’s theory of deep mediatization, which highlights how media reshape political logic and everyday communicative structures. Social media has evolved into a stage for political performance, where algorithmic visibility, affective narratives, and participatory trends are central to political appeal. Particularly on TikTok, political campaigns increasingly rely on influencers, memes, and emotional storytelling to generate virality and simulate proximity with voters.